2014
DOI: 10.1111/cogs.12108
|View full text |Cite
|
Sign up to set email alerts
|

Logical Metonymy Resolution in a Words‐as‐Cues Framework: Evidence From Self‐Paced Reading and Probe Recognition

Abstract: Logical metonymy resolution (begin a book ? begin reading a book or begin writing a book) has traditionally been explained either through complex lexical entries (qualia structures) or through the integration of the implicit event via post-lexical access to world knowledge. We propose that recent work within the words-as-cues paradigm can provide a more dynamic model of logical metonymy, accounting for early and dynamic integration of complex event information depending on previous contextual cues (agent and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…When the subject is combined with a less typical object (event or entity), no clear expectation for a verb results, leading to relatively long reading times in the self-paced reading study for an event-selecting verb. Event-based knowledge also provides an ideal candidate for the context-sensitive retrieval of the covert event as a high-typicality event involving the subject and the object of the complement coercion ( Zarcone et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the subject is combined with a less typical object (event or entity), no clear expectation for a verb results, leading to relatively long reading times in the self-paced reading study for an event-selecting verb. Event-based knowledge also provides an ideal candidate for the context-sensitive retrieval of the covert event as a high-typicality event involving the subject and the object of the complement coercion ( Zarcone et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“… Zarcone et al (2014) showed that the subject and object in a complement coercion activate a covert event matching the cued scenario. In a self-paced reading experiment in German with an explicit event ( Der Konditor begann die Glasur aufzutragen / The baker began the icing to spread ), event verb ( spread ) reading times were shorter after a high-typicality ( baker + icing ) versus a low-typicality ( child + icing ) subject–object combination.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on previously processed contextual information, a stimulus can be more or less expected. Decades of experimental work in expectation-based approaches to language processing (e.g., Altmann and Kamide, 1999 ; Trueswell et al, 1994 ; Elman et al, 2005 ) have shown that comprehenders draw context-based expectations about upcoming linguistic input at different levels: they build expectations for the next word (Morris, 1994 ; Ehrlich and Rayner, 1981 ; McDonald and Shillcock, 2003 ), but also for their phonological form (DeLong et al, 2005 ) and gender inflection (van Berkum et al, 2005 ), for syntactic parses (Spivey-Knowlton et al, 1993 ; MacDonald et al, 1994 ; Demberg and Keller, 2008 ), for discourse relations (Köhne and Demberg, 2013 ; Drenhaus et al, 2014 ; Rohde and Horton, 2014 ), for semantic categories (Federmeier and Kutas, 1999 ), for typical event participants (Bicknell et al, 2010 ; Matsuki et al, 2011 ), for the next referent to be mentioned (Altmann and Kamide, 1999 ), for the next event to happen in a sequence (Chwilla and Kolk, 2005 ; van der Meer et al, 2005 ; Khalkhali et al, 2012 ), and for typical implicit events (Zarcone et al, 2014 ). The effects of predictability are measurable, as expectation-matching input facilitates processing, and deviation from expectations produces an increase in processing costs.…”
Section: Predictability and Languagementioning
confidence: 99%
“…More recently, Zarcone and Padó (2011) and Zarcone et al (2014) brought experimental evidence for the role of Generalized Event Knowledge (GEK) (McRae and Matsuki, 2009) in the interpretation of logical metonymies. The authors refer to a long trend of psycholinguistic studies (McRae et al, 1998;Altmann, 1999;Kamide et al, 2003;McRae et al, 2005;Hare et al, 2009;Bicknell et al, 2010), which show that speakers quickly make use of their rich event knowledge during online sentence processing to build expectations about the upcoming input.…”
Section: Logical Metonymy: Psycholinguistic Evidence and Computationamentioning
confidence: 99%
“…The authors refer to a long trend of psycholinguistic studies (McRae et al, 1998;Altmann, 1999;Kamide et al, 2003;McRae et al, 2005;Hare et al, 2009;Bicknell et al, 2010), which show that speakers quickly make use of their rich event knowledge during online sentence processing to build expectations about the upcoming input. 2 The experiments on German by Zarcone et al (2014) show that the subjects combine the linguistic cues in the input to activate typical events the sentences could refer to. Given an agent-patient pair, if the covert event is typical for that specific argument combination, it is read faster and it is more difficult to inhibit in a probe recognition task.…”
Section: Logical Metonymy: Psycholinguistic Evidence and Computationamentioning
confidence: 99%